The effect of the job demand and perceived job burnout in the context of academicians’ role performance / Raja Mayang Delima Mohd Beta... [et al.] - Mohd Beta, Raja Mayang Delima; Zulkifli, Nordayana; Abd Rahim, Noor Hasvenda; Ahmad, Mumtaz; Mohamad, Masilah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
With the high demands on research outputs, academicians are under pressure to cope with their teaching responsibilities as well as other managerial and administrative responsibilities that may affect their in-role and extra-role performance.Four hundred and thirty-one (431) academicians from twenty (20) Malaysian public universities were sampled which drawn from a stratified sampling process.The study examined the factors affecting in-role and extra-role performance among academicians in Malaysian public universities. There were two (2) proposed affecting factors that being examined; namely job demands as independent factor, perceived job burnout as the mediating factor and religious personality as a moderating factor.The job demands, in-role performance and extra-role performance questionnairerevised by Bakker (2014), while the perceived job burnout questionnaire by Demerouti (2010) and religious personality questionnaire by Krauss (2007) were adopted and adapted. The Job demands-resources theory of burnout guided the study through a quantitative research design.Data were analysed using SPSS 23.0 and AMOS 23.0 approaches of structural equation modelling to test the hypothesised model. The findings of this study largely supported the hypothesised relationships proposed in the theoretical model especially the mediating effect of perceived job burnout between job demands towards in-role and extra-role performance. The study concluded that all research objectives were successfully answered and achieved.Future studies applying the proposed model are therefore recommended to be conducted at the institutions of higher learning across Malaysia in order to verify these findings.